Effects of exercise training combined with psychological intervention compared to exercise training alone in prediabetes subjects - Siyu, Yu; Hong, Liu; Qun, Yan; Hua, Qiu; Kang, Wu; Yibiao, Ding; Wenping, Wang; Qian, She; Bo, Feng; Xiaonan, Ruan (Journal of public health (Oxford, England), 2020)
Abstract Background Prior research has confirmed the efficacy of exercise training (ET) in patients with prediabetes. However, whether the effectiveness of a combination of exercise and psychological intervention (EP) is better than ET alone in prediabetes in terms of physiological function, psychological status and glycometabolism has rarely been investigated. Methods Forty newly diagnosed prediabetes patients (65.3 ± 8.1 years) took part in the study. Subjects were divided into a pure ET group and a combined EP group. Interventions were conducted in 40–50-min sessions twice weekly for 32 weeks. Physiological, psychological and biochemical indicator measurements were taken after pre-, mid- and post-interventions, respectively. Results The main finding confirmed a significant improvement in systolic blood pressure, diastolic blood pressure (DBP) and heart rate, high-density lipoprotein, fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA1c) from pre- to mid- and post-test differentially in both groups (P < 0.05) by post hoc analyses. The EP group has a greater magnitude of improvement of DBP than the ET group. Significant differences were observed in FPG at mid-intervention and total cholesterol at post-intervention between the ET and EP groups. Self-Rating Anxiety Scale (SAS) scores of EP group were significantly less than ET group after post-intervention. Conclusion Our results suggest that EP might be a promising method lead to more apparent long-term effects on glycometabolism and psychological status for prediabetes patients. Other domains were improved by both interventions, but no typical pattern could be identified. Its underlying mechanisms need further study, and directions for future research are suggested.